VATIS update : ozone layer protection. Vol. 4, No. 104, Jan-Feb 2011 - UN.ESCAP; Asian and Pacific Centre for Transfer of Technology (APCTT) (UN.ESCAP. Asian and Pacific Centre for Transfer of Technology, 2011)
VATIS Update Ozone Layer Protection is published 6 times a year to keep the readers up to date of most of the relevant and latest technological developments and events in the field of Ozone Layer Protection. The Update is tailored to policy-makers, industries and technology transfer intermediaries. Highlights : Antarctic ozone hole the smallest in five years -- Nanotechnology in refrigeration -- Perfluorocarbon solvents -- Hydrofluoroolefin blowing agent -- Clean agent fire protection system -- Fertilizer may solve methyl bromide problem THE SCIENCE OF OZONE LAYER . 4 -- Antarctic ozone hole the smallest in five years -- Ozone layer’s future linked strongly to climate change -- Ozone layer hits record thickness in Sweden ODS PHASE-OUT IN INDIA . 5 -- India-United States workshop on hydrofluorocarbons -- United States and India convene joint Task Force on HFCs -- Indian Air Force to phase out ozone depleting substances IN THE NEWS . 7 -- Governments gear up to fight environmental crimes -- South-South cooperation in the Asia-Pacific region -- European Commission pushes for carbon credit system reform -- Quality assurance and test specifications for ODS -- New technical standards for HFO-1234yf Refrigerant -- Workshop on ozone depleting HCFCs in the Philippines -- Sri Lanka acquires IP rights for ozone-friendly tea -- Brazilian company wins award for CFC-free technology -- Strong bid to find fumigant alternative REFRIGERATION/AIR-CONDITIONING . 10 -- Nanotechnology in refrigeration -- Process reclaims refrigerants to their original components -- Carbon dioxide refrigeration in containers -- Rooftop refrigeration system -- A chiller that uses 4-G HFO refrigerants -- Centrifugal chiller with magnetic bearing SOLVENTS . 12 -- Specialty vapour greaser fluid -- Zero VOC cleaner degreaser -- Flushing and cleaning alternative to ODS solvents -- Aqueous parts washing systems -- Perfluorocarbon solvents -- Environment-safe alternative to methylene chloride FOAMS . 14 -- Hydrofluoroolefin blowing agent -- Commercial ...